Social Media Marketing Activities (SMMA) As A Brand Formation Strategy A Study Of The Brand Image Formation Strategy Of Tasikmalaya Embroidery Products - Damayanti, Trie; Koswara, Aang (Jurnal Komunikasi, 2023)
Branding is an effort to establish a brand, both products, companies, and other objects. Forming a brand requires the right strategy to achieve the predefines goals, where the goal is usually quantifiable objectives. The formation of a brand will be proven by the behavior changes of the targeted public of the brand object because the branding strategy will usually be aimed at a specific public target. Social Media Marketing Activities (SMMA) is a strategy initially developed for marketers in promoting, however, its application has expanded to encompass the formation of product brands and companies. The method of writing this article is exploratory, wherein the author tries to explore the marketing activities of the embroidery industry in Tasikmalaya, which are then analyzed and associated with existing phenomena. The results indicate that SMMA is used by the embroidery industry on a large and small scale because of its ease of application, but although it is easy SMMA must be accompanied by other tools, because in forming a company brand it is not enough just to base on social media activities, but other activities that will invite public experience in interacting with these products and companies. Positive experience is the main factor in shaping the brand image of a product or company.